2010
DOI: 10.1107/s1600536810006379
|View full text |Cite
|
Sign up to set email alerts
|

Orphenadrinium picrate picric acid

Abstract: The asymmetric unit of the title compound N,N-dimethyl-2-[(2-methyl­phen­yl)phenyl­meth­oxy]ethanaminium picrate picric acid, C18H24NO+·C6H2N3O7 −·C6H3N3O7, contains one orphenadrinium cation, one picrate anion and one picric acid mol­ecule. In the orphenadrine cation, the two aromatic rings form a dihedral angle of 70.30 (7)°. There is an intra­molecular O—H⋯O hydrogen bond in the picric acid mol­ecule, which generates an S(6) ring motif. In the crystal structure, the orphenadrine cations, picrate anions and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…From the theoretical values it can be found that most of the optimized bond lengths are slightly higher than the experimental values [17,18]. The deviations can be attributed to the fact that the theoretical calculations were aimed at the isolated molecules in the gaseous phase and the experimental result was aimed at the molecule in the solid state.…”
Section: Optimized Geometrymentioning
confidence: 61%
See 1 more Smart Citation
“…From the theoretical values it can be found that most of the optimized bond lengths are slightly higher than the experimental values [17,18]. The deviations can be attributed to the fact that the theoretical calculations were aimed at the isolated molecules in the gaseous phase and the experimental result was aimed at the molecule in the solid state.…”
Section: Optimized Geometrymentioning
confidence: 61%
“…δH31-C14-H30(10), νN15-C19 (17),νN8-C12 (14) Methylene -II Scissoring , Triazole C-N stretching. 1453 1405 --νN15-C19 (17) …”
Section: (S) 1421(w)mentioning
confidence: 99%
“…The solid-state structure of orphenadrine hydrochloride and conformational comparisons with diphenhydramine hydrochloride and nefopam hydrochloride was reported (Glaser et al, 1992). The crystal structure of orphenadrinium picrate picric acid is recently reported (Fun et al, 2010). The present work reports the crystal structure of the title compound, (I), which was obtained by the interaction between orphenadrine hydrochloride and 2,4,6-trinitrophenol in aqueous medium.…”
Section: Data Collectionmentioning
confidence: 84%
“…For the pharmacological activity of the title compound, see: Hunskaar & Donnel (1991). For related structures, see: Fun et al (2010); Glaser et al (1992).…”
Section: Related Literaturementioning
confidence: 99%
“…For a clinical and pharmacological review of the efficacy of orphenadrine, see: Hunskaar & Donnel (1991). For related structures, see: Fun et al (2010); Glaser et al (1992); Jasinski et al (2011). For standard bond lengths, see Allen et al (1987).…”
Section: Related Literaturementioning
confidence: 99%